Developing Effective Arabic Speaking Skills Teaching Materials: Integrating Speech Acts in a Genre-Based Approach - Alfa Naja Imamuna; Mamluatul Hasanah; Nurhadi Nurhadi; Imam Asrori (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This research is based on the identification of issues encountered at State Islamic High School 2 Malang city, that speaking skills are often not prioritized in the classroom as evidenced by the absence of Arabic language teaching materials and the teachers' focus on reading and writing activities only. The aim of this study is to produce speaking skills teaching materials focusing on speech acts based on a genre-based approach, aligned with the learning outcomes expected by the Merdeka curriculum, and to evaluate the feasibility of these materials. This research employs a development research methodology involving five stages, which are needs analysis, design, development, feasibility testing, evaluation. Data collection techniques in this study include observation, interviews, questionnaires, and documentation. The results of the study are: 1) a speaking skills teaching materials focusing on speech acts based on a genre-based approach, incorporating various types of texts or functional communicative expressions, which is aligned with learning outcomes and student needs, and 2) the feasibility test results of the teaching materials obtained from experts reached a percentage of 87.6%, and the product readability questionnaire by students reached 81.4%. Both include to the